2012
DOI: 10.1096/fj.11-201558
|View full text |Cite
|
Sign up to set email alerts
|

A nutrient‐dense, high‐fiber, fruit‐based supplement bar increases HDL cholesterol, particularly large HDL, lowers homocysteine, and raises glutathione in a 2‐wk trial

Abstract: Dietary intake modulates disease risk, but little is known how components within food mixtures affect pathophysiology. A low-calorie, high-fiber, fruit-based nutrient-dense bar of defined composition (e.g., vitamins and minerals, fruit polyphenolics, β-glucan, docosahexaenoic acid) appropriate for deconstruction and mechanistic studies is described and evaluated in a pilot trial. The bar was developed in collaboration with the U.S. Department of Agriculture. Changes in cardiovascular disease and diabetes risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 170 publications
3
34
1
1
Order By: Relevance
“…HDL-c increased in 76% of participants, with an overall average increase of 4.1 6 1.0 mg/dl (P , 0.001), and HDL-2b increased 492 6 148 nM (P , 0.007). The additional major change observed in this study was a large increase in the adipokine adiponectin, not measured in our earlier study (51), which also increased very significantly at 2 wk (+1026 6 405 ng/ml; P , 0.002) and 8 wk (+1475 ng/ml; P = 0.005).…”
Section: Baseline Characteristics Of Lean and Ow/ob Participantssupporting
confidence: 46%
See 2 more Smart Citations
“…HDL-c increased in 76% of participants, with an overall average increase of 4.1 6 1.0 mg/dl (P , 0.001), and HDL-2b increased 492 6 148 nM (P , 0.007). The additional major change observed in this study was a large increase in the adipokine adiponectin, not measured in our earlier study (51), which also increased very significantly at 2 wk (+1026 6 405 ng/ml; P , 0.002) and 8 wk (+1475 ng/ml; P = 0.005).…”
Section: Baseline Characteristics Of Lean and Ow/ob Participantssupporting
confidence: 46%
“…Our previous report (51) indicated that twice-daily consumption of the nutrient bar for 2 wk resulted in a striking increase in most participants in HDLcholesterol (HDL-c), particularly the large HDL subfraction [designated HDL-L or HDL-2b (10.5-14.5 nm)]. HDL-2b is generally considered to be associated with less future CVD risk (52,53) and may reflect increased reverse cholesterol transport (RCT), an antiatherogenic function of HDL (54).…”
Section: Background/rationale For the Current Reportmentioning
confidence: 94%
See 1 more Smart Citation
“…It is likely that there is variation in the nutrient intake of Africans and African Americans, and this might also account for some of the differences observed in the glucose and lipid profile, including HDL size. 41 This study had limitations. First, the study design is crosssectional, so cardiometabolic events cannot be predicted with certainty.…”
Section: Discussionmentioning
confidence: 92%
“…31,33,37,40 This is of particular relevance to persons with SCI as fiber consumption has been related to levels of the cardioprotective high-density lipoprotein (HDL) cholesterol. [49][50][51][52] However, highfiber diets (20-30 g/day) may stimulate undesirable changes in bowel function that differ from the non-disabled population, which may render high fiber diets impractical for persons with SCI. 33,53,54 Future studies will need to determine the best ratio and sources for simple and complex carbohydrates that satisfy specific nutrient needs after SCI.…”
Section: Fat and Cholesterol Intakesmentioning
confidence: 99%